Teams Games Tournament Based on Cultural Exploration to Increase Students’ Emotional Intelligence - Aisyah, Riana; Wulandari, Murfiah Dewi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to determine the effectiveness of the application of the Teams Games Tournament (TGT) method based on cultural exploration in improving the emotional intelligence of elementary school students. Methodology: This study used a quantitative approach with a quasi-experiment design. The research subjects were fourth grade students of SD Muhammadiyah 1 Ketelan Surakarta, which were divided into an experimental class of 19 stu-dents by being given treatment through the cultural exploration-based Teams Games Tournament (TGT) method and a control class of 21 students using conventional learning methods. Results: The N-Gain test results showed that the experimental class obtained an aver-age N-Gain score of 76.5520, which was classified as "Effective," while the control class only achieved an average score of 32.9558, which was catego-rized as "Not Effective." These results indicate that the cultural exploration-based Teams Games Tournament (TGT) method is significantly effective in improving students' emotional intelligence. Applications/Originality/Value: This study also contributes to the use of game-based learning strategies as an effort to develop emotional intelligence among elementary school students.